Non-immunogenic staphylokinase in the high-risk pulmonary embolism treatment with subdural hematoma - S. L. Konstantinov; Zh. Yu. Chefranova; G. I. Stryabkova; S. A. Pribylov; I. B. Kovalenko; E. V. Gavrilyuk; S. V. Ivanov; S. S. Markin (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the safety and efficacy of the non-immunogenic staphylokinase in a patient with a massive high-risk pulmonary embolism (PE) with subdural hematoma.Material and methods. Non-immunogenic staphylokinase (Fortelyzin®, LLC “SuperGene”, Russia) is an original thrombolytic drug with high fibrin selectivity and minimal risk of bleeding. A clinical case of the non-immunogenic staphylokinase usage at a dose of 15 mg as a single bolus in an elderly patient with massive high-risk PE with subdural hematoma is presented.Results. Thrombolytic therapy with the non-immunogenic staphylokinase was performed in an 85-years old female with very high mortality risk PE (PESI class V) associated with acute subdural lamellar hematoma, resulting from closed craniocerebral injury. In the first day after thrombolytic therapy, a decrease dyspnea, increase saturation from 74% to 97%, decrease pulmonary artery pressure from 60 to 31 mm Hg, and reduce of right ventricular dysfunction were noted. According to brain CT, on the first day after thrombolysis, an increase in the volume of the subdural hematoma (maximum thickness 8 mm) without dislocation syndrome and without focal neurological deficit was registered. After one week, the patient was discharged. At the follow-up examination after 4 months, regression of the subdural hematoma was noted (the thickness less than 2 mm). The non-immunogenic staphylokinase usage did not lead to major bleeding and hemorrhagic stroke.Conclusion. The non-immunogenic staphylokinase has shown safety and efficacy in massive PE treatment in an elderly patient with high hemorrhagic risk due to a subdural hematoma.